Assessement of glycaemia and serum activities of aspartate aminotransferase, creatinekinase, gamma glutamyltransferase and lactate dehydrogenase in thoroughbred horses submitted to exercise of different intensities - Balarin, Mara Regina Stipp; Lopes, Raimundo Souza; Kohayagawa, Aguemi; Laposy, Cecília Braga; Fonteque, Joandes Henrique (Semina: Ciências Agrárias, 2005)
In order to evaluate the influence of exercise of different intensities on biochemical parameters in Thoroughbred horses blood was collected from 60 animals, 30 males and 30 females.The animals were subdivided in two groups : 30 horses, 15 males and 15 females with 24 to 36 months of age and not in training, and after 12 months of training; 30 horses, 15 males and 15 females with 36 to 48 months of age in training. Blood samples were collected before and after trot and gallop. Plasmatic glucose was analyzed through a colorimetric method, while aspartate aminotransferase (AST), creatine kinase (CK), lactate dehydrogenase (LDH) and gammaglutamyltransferase (GGT) were analyzed through kinetic methods. Results show a statistically significant increase in plasmatic glucose after trot and gallop independent of gender, while the increases in CK and LDH were different for males and females. Variations for AST and GGT were not statistically significant.